Minat Generasi Z di Kabupaten Aceh Barat untuk Berkunjung ke Destinasi Wisata Sejarah Makam Teuku Umar - Qudus, Sultan Ruhil; Yusnaidi, Yusnaidi (Jurnal Ilmiah Ekonomi Terpadu (Jimetera), 2024)
As the heirs of civilization, Generation Z exhibits interest in visiting historical tourist destinations, demonstrating that they still harbor a sense of nationalism that never forgets the history of heroes. As Bung Karno once said, "A great nation is a nation that can appreciate the services of its heroes." The interest of generation Z in visiting the historical tourism site of Teuku Umar's mausoleum in the West Aceh area is measured using the theory of planned behavior (TPB). In this study, which employs a quantitative methodology, a sample of 96 respondents provided the primary data. The findings of this study show that generation Z's attitude, subjective norm and  perceived behavioral control have direct positive effect on  generation Z's  behaviour intention to visit  Teuku Umar’s grave in the West Aceh district.